Modernity / coloniality, extractivism and biocultural memory. In search of lost roads - Patricia Agosto (Revista Kavilando, 2018)
Nature and women have undergone a process of coloniality and domination, which has twinned them in their resistance, their struggles and their alternative constructions to global and extractivist capitalism. That coloniality, which was born with the conquest of our continent by the European expansion, continues in Latin American extractivism, which does nothing but subject nature and populations to an irrational exploitation, converting both to the sacrifice of being the suppliers of natural commons that maintain the game in the world market, recreating a role that is more than 500 years old. Faced with a multidimensional global crisis that brings into play the very existence of life on the planet, new alternative paths are proposed that lead to decolonization, de-patriarchalization and decapitalization. The recovery and revalorization of the biocultural memory of the human species, with respect for territorial and social diversity as a standard, is one of them.